PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ADOBE ANIMATE (FORZA) PADA MATERI GAYA MENINGKATKAN PRESTASI BELAJAR IPAS SD KELAS IV - Apriansyah, Wira; Wahyudi, Urip Muhayat Wiji (STKIP Persada Khatulistiwa Sintang, 2026)
This study aimed to examine how the interactive learning media FORZA can improve the academic performance of fourth-grade students at SDN Kadipiro, Yogyakarta, on the topic of forces (IPAS). Conducted in 2026, the research employed the ADDIE development model. The product, FORZA media, was tested through two stages: a limited trial and a field test. Data were collected through interviews, questionnaires, and pretest–posttest assessments. The results showed that the FORZA application was highly effective. Media experts rated it at 87.1% and subject-matter experts at 91.1%, both categorizing it as highly feasible. Teachers and students also considered the media practical, with scores of 77% and 72%, respectively. Furthermore, students’ test scores increased by 20% after using the media. In conclusion, the FORZA interactive learning media is feasible, practical, and effective in improving students’ learning outcomes in elementary science (IPAS).